The influence of sleep disturbances on the development of insulin resistance - a literature review - Anna Chmura; Katarzyna Skowrońska; Anna Karaś; Patrycja Baciur; Filip Białas (Kazimierz Wielki University, 2022)
Introduction and purpose of the work: Sleep is essential for the proper functioning of the body. Adequate quality and quantity of sleep affects metabolic processes, including glucose metabolism, as well as the sensitivity of tissues to insulin, the reduction of which is called insulin resistance. It leads to an increased production of glucose in order to maintain normal blood glucose levels. Insulin resistance is a modifiable risk factor of, inter alia, type 2 diabetes. The aim of this study is to summarize the current knowledge on the relationship between sleep deprivation and an increased risk of developing insulin resistance. State of knowledge: Sleep undoubtedly has a strong influence on glucose metabolism and insulin sensitivity. Numerous studies show that even partial sleep deprivation lowers insulin sensitivity. The available literature shows that shift work and a shifted bedtime, combined with an insufficient amount of it, lead to a significant reduction in insulin sensitivity. The positive effect of increasing the time of night rest on the sensitivity of tissues to insulin may be an element of the prevention of diseases such as obesity or type 2 diabetes. Moreover, disturbances in sleep continuity lead to formation of insulin resistance. An example would be obstructive sleep apnea, the treatment of which affects metabolic processes. Summary: Adequate sleep hygiene is an extremely important part of a healthy lifestyle. More research is needed on the relationship between sleep and the regulation of carbohydrate metabolism, due to the fact that the appropriate sleep-wake rhythm may give hope for improvement in health in people with metabolic disorders and may be an important protective factor for many diseases.